PERMAINAN TEBAK KATA BAHASA ACEH MENGGUNAKAN ALGORITMA TURBO BOOYER-MOORE - Rizal Rizal (TECHSI - Jurnal Teknik Informatika, 2019)
word guessing game is one of the most popular game today. No age limit, This game is free to play anyone. Besides useful to increase knowledge of vocabulary, word guessing game is also able to provide entertaiment. Simlarly, word guessing game aceh language is able to provide entertainment and insight vocabulary which in many communities currently blind eye on their own local language. To build applications this game needed a method. One method that can be applied to word guessing game is a string matching. String matching is a process commonly performed computer. One of it is the search and matching text. There are several algorithms that can address these problems, one of it is the algorithm Turbo Boyer-Moore. From the research conducted, it can be concluded that the Algorithm Boyer-Moore is the fastest algorithm in the matching string.